Media as a Political Tool: Comparative Study Between Indonesia and Saudi Arabia - Khalid Vikriadi; Ainiyatul Latifah; Riky Ovaliansyah Harahap; Tiara Ramadhani; Aubaidillah Doloh; Nurul Kamaly (JOURNAL OF SOCIETY INNOVATION AND DEVELOPMENT, 2026)
While media freedom is traditionally framed within a democracy-authoritarianism dichotomy, emerging patterns of digital control suggest that state-media interactions are becoming increasingly complex. This study addresses the background problem of how varied political regimes in Muslim-majority nations instrumentalize media to maintain legitimacy and manage public discourse. The primary research objective is to develop a cross-regime typology by comparing media control mechanisms in Indonesia, an electoral democracy, and Saudi Arabia, an absolute monarchy. Utilizing a qualitative comparative case study design, the methodology involves the thematic analysis of official legal frameworks, international press freedom reports, and digital archive data from 2019 to 2025. The key findings reveal that Indonesia employs "competitive digital manipulation," where democratic legal apparatuses like the ITE Law are weaponized for "soft" repression and self-censorship. Conversely, Saudi Arabia utilizes "legal-institutional control," relying on absolute monarchical authority and pervasive surveillance to systematically dismantle independent dissent. The findings imply that a state’s "digital legal architecture" is a more significant predictor of media autonomy than formal regime labels. This research contributes to the field of political communication and democracy in a Muslim and Muslim majority country by providing a nuanced framework for understanding how power is consolidated through media in diverse institutional configurations, suggesting that democratic backsliding often manifests through the legalistic erosion of the digital public sphere.